Microclimate of Brown Bear (Ursus arctos L.) Dens and Denning Area - Damir Ugarković; Nikolina Kelava Ugarković (Animals, 2024)
The aim of this study was to determine the microclimate of brown bear dens depending on their size, their status (active or inactive), and the location of the den. The study included five dens of different sizes and locations in the Velebit Mountains, in the Dinaric Alps. The measurements of air temperature (°C) and relative humidity (%) in dens and the forest stands were carried out over 182 days. The absolute minimum air temperature in inactive dens was between −2.88 °C and −0.38 °C and belonged to the dens with shorter tunnels and without chambers. The exception was inactive den 1, which was situated in a thermophilic forest. No negative absolute minimum air temperatures were recorded in active dens. The absolute minimum air temperatures in the forest stands were lower than in the dens. The relative humidity was significantly higher in all dens than in the forest stands. Dens with a large entrance opening and a short tunnel were strongly influenced by the local microclimate of the forest stand. The greatest temperature difference (den–forest) was between elongated dens with chambers and the associated forest stand, while the smallest temperature differences occurred in dens with a short tunnel, without a chamber, and at the northern exposure. The greatest differences in relative humidity (den–forest) were found in dens with chambers. The den temperatures correlated with the air temperatures in the forest stands.